Green conversion of crop residues into porous carbons and their application to efficiently remove polycyclic aromatic hydrocarbons from water: Sorption kinetics, isotherms and mechanism. (July 2019) - Cheng, Hu; Bian, Yongrong; Wang, Fang; Jiang, Xin; Ji, Rongting; Gu, Chenggang; Yang, Xinglun; Song, Yang
Graphical abstract: Highlights: Rape straw- and corn cob-derived porous carbons were prepared and characterized. KHCO3 activation of hydrochar was an efficient method to develop pore structure. The porous carbons exhibited superior sorption capabilities to PAHs. Possible sorption mechanisms were explained by kinetic and isotherm studies. Abstract: In this study, rape straw- and corn cob-derived porous carbons (PCs) were fabricated by hydrothermal treatment (250 °C, 4 h) and subsequent activation (850 °C, 1 h) using a non-corrosive agent, potassium bicarbonate. The PCs exhibited a very large specific surface area (1069–1281 cm 2  g −1 ), high pore volume (0.55–0.72 cm 3  g −1 ), wide pore size distribution (from micropores to macropores), high hydrophobicity, and partly graphitized structure. These properties contributed to highly efficient performance for the sorption of polycyclic aromatic hydrocarbons (PAHs), with maximum sorption capacities of 592.97, 480.27, and 692.27 mg g −1 towards naphthalene, acenaphthene, and phenanthrene, respectively. A three-step sorption process with pore filling, hydrophobic effects, and π-π stacking interactions on the heterogeneous surface is a possible mechanism for the sorption of PAHs onto PCs. This study presents an environmentally friendly strategy for the reuse of crop residues in the field of organic micropollutant-contaminated water treatment.